2007
DOI: 10.1007/s00128-007-9314-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Synthetic Pyrethroid Cypermethrin to Some Freshwater Organisms

Abstract: Ninety-six hours static bioassays were made in the laboratory to determine acute toxicity of cypermethrin to five non-target freshwater organisms belonging to different taxa and niche. Susceptibility of the organisms to cypermethrin was in the order: the crustacean Diaptomus forbesi > the aquatic insect Ranatra filiformis > the freshwater carp Cyprinus carpio > the tadpole larva of the toad Bufo melanostictus > the oligochaet worm Branchiura sowerbyi. Ninety-six hours LC50 values of aqueous cypermethrin ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 10 publications
1
46
1
Order By: Relevance
“…Besides, the 96 h LC 50 values of beta-cypermethrin to L. vannamei at either 5.0% or 20.0% in this study were much lower than the LC 50 values reported in fishes (Table 3), such as Cyprinus carpio [9,11], Oncorhynchus mykiss [9], Salmo trutta [9], Salmo salar [8], Poecilia reticulata [10], Gambusia affinis [8], Cyprinodon macularius [8]. For Acephate, the toxicity to L. vannamei at either salinity and to other crustacean species, including A. bahia [19], H. americanus [19], P. aztecus [18], and P. duorarum [19] were also much lower than the values reported in fishes [18,19,34].…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…Besides, the 96 h LC 50 values of beta-cypermethrin to L. vannamei at either 5.0% or 20.0% in this study were much lower than the LC 50 values reported in fishes (Table 3), such as Cyprinus carpio [9,11], Oncorhynchus mykiss [9], Salmo trutta [9], Salmo salar [8], Poecilia reticulata [10], Gambusia affinis [8], Cyprinodon macularius [8]. For Acephate, the toxicity to L. vannamei at either salinity and to other crustacean species, including A. bahia [19], H. americanus [19], P. aztecus [18], and P. duorarum [19] were also much lower than the values reported in fishes [18,19,34].…”
Section: Resultscontrasting
confidence: 84%
“…Due to the Lipophilicity, Pyrethroids have a high rate of gill absorption. So they have been reported to be extremely toxic to fish [8][9][10][11][12], but information in crustacean species is still limited. Acephate is a water soluble foliar spray insecticide of moderate persistence and is used on fruit and vegetable crops grown across the world [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although pyrethroid pesticides generally have lower acute oral mammalian toxicity than organophosphate insecticides, exposure to very high levels of pyrethroid pesticides might cause endocrine disruption, lymph node and spleen damage, and carcinogenesis (6,12). In addition, most pyrethroid pesticides possess acute toxicity to some nontarget organisms, such as bees, fish, and aquatic invertebrates, often at concentrations of less than 0.5 g/kg (19,22). Great concerns have been raised about the persistence and degradation of pyrethroid pesticides in the environment.…”
mentioning
confidence: 99%
“…But information on the toxicity of these pesticides to non-target aquatic organisms is scarce. Cypermethrin has already been reported as highly toxic to fish (Kumar et al 2007;Saha and Kaviraj 2008). Sporadically, it has also been reported that the toxicity of cypermethrin to fish varies with stereochemical structure (Polat et al 2002), mixtures of their isomers (Yilmaz et al 2004) and formulation.…”
Section: Introductionmentioning
confidence: 99%